Implementation of Corporate Governance in Fraud Prevention in Islamic Banking - Uus Ahmad Husaeni; Reksa Jayengsari (Fakultas Hukum Universitas Mataram, 2020)
The purpose of this article is to analyze the implementation of Bank Indonesia regulations on corporate governance for Islamic banking so as to avoid fraud. The research method in this article is a qualitative research method. The data sources of this article are primary data and secondary data. Primary data was obtained from field research on several Islamic banks, the Financial Services Authority (OJK), and the Corruption Eradication Commission of the Republic of Indonesia (KPK) who were respondents. The secondary data in the form of legislation regarding corporate governance and those related to sharia banking corporate governance, also data on research results from international journals, as well as other relevant literature. The results of the study show that the regulations issued by Bank Indonesia regarding corporate governance for Islamic banking are not in accordance with the provisions of positive law and Islamic law, and there are provisions that allow fraud. Because there is no philosophical basis, there are weaknesses in some juridical aspects, and contain sociological weaknesses.